US Import Refusals of Agricultural Products and Their Impact on the Participation of Indian Firms. (April 2018) - Kallummal, Murali; Mendiratta, Disha; Sangita, Seema
Developed countries are major importers of agricultural and food products from developing countries. While international trade in agricultural commodities has expanded, there has been growing consciousness by consumers about the quality of imported food products. The WTO members are legally authorized to impose sanitary and phytosanitary (SPS)-based maximum residual level (MRL) standards on imported food products to ensure that the imports are free from contaminants. Compliance with SPS-based standards and regulations is challenging for firms belonging to developing countries, for reasons including information asymmetry and lack of technological capabilities. This article uses data on Indian firms, and the SPS measures imposed by the USA on Indian products to analyse how SPS measures impact on the performance of firms, especially on the probability of the firms to participate in the export market and their export earnings. We find that the presence of standards discourages firms to participate in the export market. However, bigger firms are more productive and able to absorb the impact of SPS measures and continue to participate in export markets, even in the presence of these regulations.